The quick pivot: Capturing real world modifications for the re-implementation of an early psychosis program transitioning to virtual delivery - Tempelaar, Wanda; Kozloff, Nicole; Crawford, Allison; Voineskos, Aristotle; Addington, Don; Alexander, Tallan; Baluyut, Crystal; Bromley, Sarah; Brooks, Sandy; de Freitas, Lauren; Jindani, Seharish; Kirvan, Anne; et al. (Frontiers in Health Services, 2023)
Background Team-based Early Psychosis Intervention (EPI) services is standard of care for youth with psychosis. The COVID-19 pandemic required most EPI services to mount an unplanned, rapid pivot to virtual delivery, with limited guidance on how to deliver virtual clinical services or whether quality of re-implementation and treatment outcomes would be impacted. We used a structured approach to identify essential modifications for the delivery of core components and explored facilitators and barriers for re-implementation and fidelity of a virtually delivered EPI intervention. Materials and methods NAVIGATE is a structured approach to team-based EPI. It provides detailed modules to guide delivery of core components including medication management, psychoeducation and psychotherapies, supported employment/education, and family education. Having initially implemented NAVIGATE at the Centre for Addiction and Mental Health (CAMH) in 2017, the EPI service transitioned to virtual delivery amid the COVID pandemic. Using a practice profile developed to support implementation, we detailed how core components of NAVIGATE were rapidly modified for virtual delivery as reported in structured group meetings with clinicians. The Framework for Reporting Adaptations and Modifications for Evidence-Based Interventions (FRAME) was used to describe modifications. Fidelity to the EPI standards of care was assessed by the First Episode Psychosis Fidelity Scale (FEPS-FS). Re-implementation barriers and facilitators and subsequent mitigation strategies were explored using structured clinician interviews guided by the Consolidated Framework for Implementation Research (CFIR). Results Identified modifications related to the intervention process, context, and training. We identified contextual factors affecting the re-implementation of virtually delivered NAVIGATE and then documented mitigating strategies that addressed these barriers. Findings can inform the implementation of virtual EPI services elsewhere, including guidance on processes, training and technology, and approaches to providing care virtually. Discussion This study identified modifications, impacts and mitigations to barriers emerging from rapid, unplanned virtual delivery of EPI services. These findings can support delivery of high-quality virtual services to youth with psychosis when virtual care is indicated.